Nanometer modified internal curing high-geothermal-resistance full-hole slag concrete and preparation method thereof
Patent Information
- Application Number
- CN202410721410.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-05
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-06-05
AI Technical Summary
本发明所得全洞渣混凝土具有良好的力学性能以及耐高地热性能等特点,能够改善隧道高地热所带来混凝土服役性能下降问题,实现了隧道混凝土的耐高地热使用需求,解决了隧道结构因高地热而引起的混凝土开裂问题,使隧道结构建筑物服役寿命大幅提高,具有重要的实际应用价值
[0019]高地热是造成隧道混凝土材料病害的关键因素之一。高地热环境通过影响混凝土内部的物相演变,改变水化产物组成,导致混凝土孔隙率增加、孔径增大,严重影响混凝土的力学性能和耐久性能。本发明采用洞渣制备的石粉与机制砂制备出全洞渣混凝土,在此基础上进行的性能提升,其中以隧道洞渣石粉为粉料取代水泥,辅以纳米Al2O3密实填充,纳米Al2O3的添加还有助于提高水化初期钙矾石的生成量,从而避免高地热环境下钙矾石数量的急剧减少,在减少CO2排放的同时提高水泥基材料整体密实度;同时掺入水玻璃改性吸水性树脂,利用其内养护作用改善混凝土的后期服役性能;此外,本发明所述纳米改性全洞渣内养护耐高地热混凝土具有良好的工作性能和力学性能,隧道洞渣石粉、纳米材料与吸水性树脂紧密堆积且分布均匀,保障了隧道用纳米改性全洞渣内养护耐高地热混凝土具有良好的服役性能,为隧道服役寿命提供了保障。
Smart Images

Figure CN118495910B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high geothermal environment resistant silicate cement-based materials for tunnels, specifically relating to a nano-modified internal curing high geothermal whole-tunnel slag concrete and its preparation method. Background Technology
[0002] With the deepening utilization of underground space in my country, the types and number of geological hazards faced by underground structures are gradually increasing. Among them, high geothermal activity is a critical issue that urgently needs to be addressed in tunnel construction, attracting widespread attention. High geothermal environments affect the hydration products and microstructure of concrete, degrading its mechanical properties and seriously jeopardizing the safety of tunnel structures. Furthermore, the application of tunnel slag powder and manufactured sand in tunnel concrete is currently limited. The low activity and large particle size of tunnel slag make it difficult for concrete to meet the required mechanical properties and high geothermal resistance. Therefore, an improved technical solution is needed to address the shortcomings of existing technologies. Based on this, this invention provides a nano-modified, internally cured, high geothermal resistant whole-slag concrete and its preparation method, which exhibits excellent high geothermal resistance, effectively improving the service life of tunnel structures and reducing maintenance costs, thus meeting the durability requirements of tunnel concrete. Summary of the Invention
[0003] To address the problems existing in the prior art, the present invention aims to provide a nano-modified, internally cured, high-geothermal-resistant full-cavity slag concrete and its preparation method. The full-cavity slag concrete obtained by this invention possesses excellent mechanical properties and high-geothermal-resistance performance, which can improve the problem of reduced concrete service performance caused by high geothermal heat in tunnels, meet the high-geothermal-resistance requirements of tunnel concrete, solve the problem of concrete cracking caused by high geothermal heat in tunnel structures, and significantly extend the service life of tunnel structures, thus possessing significant practical application value.
[0004] To achieve the above objectives, the present invention provides the following technical solution:
[0005] This invention relates to a nano-modified internal curing high geothermal resistant full-cavity concrete, comprising the following raw materials in parts by weight: 200-500 parts silicate cement, 10-250 parts tunnel cavity powder, 900-1800 parts manufactured sand from tunnel cavities, 1-20 parts nano Al2O3, 0.1-2 parts water-absorbing resin, 1-20 parts water glass, and 200-300 parts water.
[0006] Preferably, the raw materials include the following parts by weight: 240-432 parts silicate cement, 48-240 parts tunnel slag powder, 900-1800 parts manufactured sand for tunnel slag, 1.5-3.5 parts nano Al2O3, 0.2-0.6 parts water-absorbing resin, 5-15 parts water glass, and 200-300 parts water.
[0007] Preferably, by mass percentage, the mass of tunnel slag powder is 1% to 50% of the total mass of silicate cement and tunnel slag powder; the mass of nano-Al2O3 is 0.1% to 5% of the powder mass; the mass of water-absorbing resin is 0.01% to 0.5% of the powder mass; the mass of water glass is 0.1% to 5% of the powder mass; and the mass ratio of manufactured sand to powder is (2 to 3):1, wherein the powder is silicate cement and tunnel slag powder.
[0008] Preferably, by mass percentage, the mass of tunnel slag powder is 10% to 50% of the total mass of silicate cement and tunnel slag powder; the mass of nano-Al2O3 is 0.3% to 0.7% of the powder mass; the mass of water-absorbing resin is 0.04% to 0.1% of the powder mass; and the mass of water glass is 1% to 3% of the powder mass.
[0009] Preferably, the silicate cement is ordinary silicate cement with P·O 42.5.
[0010] Preferably, the specific surface area of the tunnel slag powder is ≥500m². 2 / kg, CaCO3 mass content ≥85%; the particle size of the tunnel slag manufactured sand is 0.5mm-5mm.
[0011] Preferably, the nano-Al2O3 has a particle size of 10-100 nm and a purity of ≥99%.
[0012] Preferably, the particle size of the water-absorbing resin is 50-150 mesh.
[0013] Preferably, the water glass has a modulus of 3.3 and a solid content of 34%.
[0014] This invention provides a method for preparing the aforementioned nano-modified internally cured high-geothermal-resistant full-cavity slag concrete, comprising the following steps:
[0015] (1) Weigh each raw material according to the proportions and set aside;
[0016] (2) Take out half the mass of water first, and fully dissolve the nano-Al2O3 in the mixed solution of water glass and half the mass of water to obtain the nano-Al2O3 dispersion for later use;
[0017] (3) Mix silicate cement, tunnel slag powder, nano Al2O3 dispersion, water-absorbing resin and tunnel slag manufactured sand, dry mix for 1 to 2 minutes, then add the remaining amount of water and stir for 2 to 4 minutes to obtain the final product.
[0018] Beneficial effects:
[0019] High geothermal temperatures are one of the key factors causing defects in tunnel concrete materials. High geothermal environments affect the phase evolution inside concrete, altering the composition of hydration products, leading to increased porosity and larger pore sizes, which seriously affects the mechanical and durability properties of concrete. This invention utilizes tunnel slag powder and manufactured sand to prepare full-slag concrete. Performance improvements are then made by replacing cement with tunnel slag powder and supplementing it with nano-Al2O3 for dense filling. The addition of nano-Al2O3 helps increase the formation of ettringite in the early stages of hydration, thus preventing a sharp decrease in ettringite quantity under high geothermal conditions. This reduces CO2 emissions while increasing the overall density of the cement-based materials. Simultaneously, water glass-modified absorbent resin is incorporated to improve the later-stage service performance of the concrete through its internal curing effect. Furthermore, the nano-modified full-slag internal-cured high-geothermal-resistant concrete described in this invention exhibits excellent workability and mechanical properties. The tunnel slag powder, nanomaterials, and absorbent resin are tightly packed and uniformly distributed, ensuring good service performance of the nano-modified full-slag internal-cured high-geothermal-resistant concrete for tunnels and guaranteeing the service life of the tunnel.
[0020] The nano-modified, fully-cured, geothermal-resistant concrete provided by this invention possesses excellent geothermal resistance and good mechanical properties, improving the durability of concrete structures and significantly extending the service life of buildings. This addresses the technical challenge of achieving high durability requirements for tunnel concrete. The preparation method and construction process described in this invention are simple, easy to operate, and have practical application value. Attached Figure Description
[0021] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. Wherein:
[0022] Figure 1 Scanning electron microscope image of tunnel slag powder (4000×, 40μm).
[0023] Figure 2 This is a particle size distribution diagram of tunnel slag powder.
[0024] Figure 3 This is an XRD analysis diagram of tunnel slag powder.
[0025] Figure 4 Scanning electron microscope image of silicate cement (1000×, 100μm).
[0026] Figure 5 This is a particle size distribution diagram of silicate cement.
[0027] Figure 6 This is the XRD analysis diagram of silicate cement.
[0028] Figure 7 This is a scanning electron microscope image (800×, 200μm) of the full-cavity slag concrete obtained in Comparative Example 2 of the present invention.
[0029] Among them, (a) is standard curing (20℃) for 28 days; (b) standard curing (20℃) for 1 day followed by high geothermal (65℃) for 28 days; (c) standard curing (20℃) for 1 day followed by high geothermal (105℃) for 28 days; Figure 8-12 same.
[0030] Figure 8 The image shows a scanning electron microscope (8000×, 20μm) image of the full-cavity slag concrete obtained in Comparative Example 2 of this invention.
[0031] Figure 9 The image shows a scanning electron microscope (30000×, 5μm) image of the full-cavity slag concrete obtained in Comparative Example 2 of this invention.
[0032] Figure 10 The image shows a scanning electron microscope (800×, 200μm) image of the full-cavity slag concrete obtained in Example 2 of this invention.
[0033] Figure 11 The image shows a scanning electron microscope (8000×, 20μm) image of the full-cavity slag concrete obtained in Example 2 of this invention.
[0034] Figure 12 The image shows a scanning electron microscope (30000×, 5μm) image of the full-cavity slag concrete obtained in Example 2 of this invention. Detailed Implementation
[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.
[0036] The present invention will now be described in detail with reference to embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.
[0037] This invention addresses existing problems by providing a nano-modified, internally cured, high-geothermal-resistant tunnel slag concrete, comprising the following raw materials in parts by weight: 200-500 parts of silicate cement (e.g., 200, 240, 288, 336, 384, 432, or 500 parts), 10-250 parts of tunnel slag powder (e.g., 10, 30, 48, 96, 144, 192, or 240 parts), 900-1800 parts of manufactured tunnel slag sand (e.g., 900, 1100, 1300, 1500, or 1800 parts), and nano-Al2O3. 1 to 20 parts (e.g., 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 5 parts, 15 parts or 20 parts), 0.1 to 2 parts of absorbent resin (e.g., 0.1 parts, 0.2 parts, 0.4 parts, 0.6 parts, 1 part or 2 parts), 1 to 20 parts of water glass (e.g., 1 part, 5 parts, 10 parts, 15 parts or 20 parts), and 200 to 300 parts of water (e.g., 200 parts, 230 parts, 260 parts or 300 parts).
[0038] In a preferred embodiment of the present invention, the raw materials include the following parts by weight: 240-432 parts of silicate cement (e.g., 240 parts, 288 parts, 336 parts, 384 parts, or 432 parts), 48-240 parts of tunnel slag powder (e.g., 48 parts, 96 parts, 144 parts, 192 parts, or 240 parts), 900-1800 parts of manufactured tunnel slag sand (e.g., 900 parts, 1100 parts, 1300 parts, 1500 parts, or 1800 parts), and nano-Al2O3. 1.5 to 3.5 parts (e.g., 1.5, 2, 2.5, 3 or 3.5 parts), 0.2 to 0.6 parts of water-absorbing resin (e.g., 0.2, 0.4 or 0.6 parts), 5 to 15 parts of water glass (e.g., 5, 10 or 15 parts) and 200 to 300 parts of water (e.g., 200, 230, 260 or 300 parts).
[0039] In a preferred embodiment of the present invention, the mass percentage of tunnel slag powder is 1% to 50% (e.g., 1%, 5%, 10%, 20%, 30%, 40%, or 50%) of the total mass of silicate cement and tunnel slag powder; the mass percentage of nano-Al2O3 is 0.1% to 5% (e.g., 0.1%, 0.3%, 0.5%, 0.7%, 1%, 3%, or 5%) of the powder mass; and the mass percentage of water-absorbing resin is 0.01% to 5% of the powder mass. 0.5% (e.g., 0.01%, 0.04%, 0.06%, 0.08%, 0.1%, 0.3%, or 0.5%); the mass of water glass is 0.1% to 5% of the powder mass (e.g., 0.1%, 0.5%, 1%, 2%, 3%, or 5%); the mass ratio of manufactured sand to powder in tunnel slag is (2-3):1 (e.g., 2:1, 2.3:1, 2.7:1, or 3:1), and the powder is silicate cement and tunnel slag powder.
[0040] In a preferred embodiment of the present invention, the mass percentage of tunnel slag powder is 10% to 50% (e.g., 10%, 20%, 30%, 40%, or 50%) of the total mass of silicate cement and tunnel slag powder; the mass percentage of nano-Al2O3 is 0.3% to 0.7% (e.g., 0.3%, 0.5%, or 0.7%) of the powder; the mass percentage of water-absorbing resin is 0.04% to 0.1% (e.g., 0.04%, 0.06%, 0.08%, or 0.1%) of the powder; the mass percentage of water glass is 1% to 3% (e.g., 1%, 2%, or 3%) of the powder; and the mass ratio of manufactured sand to powder is (2-3):1 (e.g., 2:1, 2.3:1, 2.7:1, or 3:1), wherein the powder is silicate cement and tunnel slag powder.
[0041] In a preferred embodiment of the present invention, the silicate cement is ordinary silicate cement with P·O 42.5.
[0042] In a preferred embodiment of the present invention, the specific surface area of the tunnel slag powder is ≥500m². 2 / kg, CaCO3 mass content ≥85%; the particle size of the tunnel slag manufactured sand is 0.5mm-5mm.
[0043] In a preferred embodiment of the present invention, the particle size of the nano-Al2O3 is 10-100 nm and the purity is ≥99%.
[0044] In a preferred embodiment of the present invention, the particle size of the water-absorbing resin is 50-150 mesh.
[0045] In a preferred embodiment of the present invention, the water glass has a modulus of 3.3 and a solid content of 34%.
[0046] This invention provides a method for preparing nano-modified internally cured, high-geothermal-resistant, full-cavity slag concrete, comprising the following steps:
[0047] (1) Weigh each raw material according to the proportions and set aside;
[0048] (2) Take out half the mass of water and use a magnetic stirrer to fully dissolve the nano-Al2O3 in the mixed solution of water glass and half the mass of water to obtain a nano-Al2O3 dispersion for later use.
[0049] (3) Pour silicate cement, tunnel slag powder, nano Al2O3 dispersion, water-absorbing resin and tunnel slag manufactured sand into a concrete mixer and dry mix for 1 to 2 minutes (e.g., 1 minute, 1.5 minutes or 2 minutes). Then add the remaining amount of water and mix for 2 to 4 minutes (e.g., 2 minutes, 3 minutes or 4 minutes) to obtain the final product.
[0050] The following detailed description of a nano-modified internal curing high geothermal resistant full-cavity slag concrete and its preparation method, through specific embodiments, provides a detailed explanation of the present invention.
[0051] The raw materials used in the following examples:
[0052] The silicate cement is ordinary silicate cement with P·O 42.5.
[0053] The tunnel muck is composed of dolomite lithology. First, a double-roller mill is used to crush the tunnel muck to obtain manufactured sand. Then, the coarsely crushed tunnel muck is fed into a ball mill for grinding to obtain tunnel muck powder. The specific surface area of the tunnel muck powder is ≥500 m². 2 / kg, CaCO3 mass content ≥85%. The particle size of the manufactured sand for tunnel muck is 0.5mm-5mm.
[0054] The particle size of nano-Al2O3 is 10-100 nm, and the purity is ≥99%.
[0055] The particle size of the water-absorbing resin is 50-150 mesh.
[0056] The water glass has a modulus of 3.3 and a solid content of 34%.
[0057] Among them, the microstructure of tunnel muck powder is as follows: Figure 1 As shown, the particle size distribution of tunnel slag powder is as follows: Figure 2 As shown, the phase composition of tunnel muck powder is as follows: Figure 3 As shown. The microstructure of silicate cement is as follows. Figure 4 As shown, the particle size distribution of silicate cement is as follows: Figure 5 As shown, the phase composition of silicate cement is as follows: Figure 6 As shown.
[0058] Depend on Figure 1-6 It is known that, compared with silicate cement, tunnel slag powder has a larger particle size and is mainly composed of Dolomite, which is difficult to react. Therefore, it has a significant impact on the mechanical properties and high geothermal resistance of concrete. It is necessary to optimize the mechanical properties and high geothermal resistance of tunnel slag concrete.
[0059] Example 1
[0060] This embodiment provides a nano-modified internal curing high geothermal resistant full-cavity concrete, comprising the following raw materials in parts by weight: 432 kg of ordinary silicate cement, 48 kg of tunnel cavity powder, 1300 kg of manufactured sand from tunnel cavities, 260 kg of water, 2.5 kg of nano-Al2O3, 0.4 kg of water-absorbing resin, and 10 kg of water glass.
[0061] Specifically, by mass percentage, the mass of tunnel slag powder is 10% of the total mass of silicate cement and tunnel slag powder; the mass of nano-Al2O3 is 0.5% of the powder mass; the mass of water-absorbing resin is 0.08% of the powder mass; the mass of water glass is 2% of the powder mass; and the mass ratio of manufactured tunnel slag sand to powder is 2.7:1, wherein the powder consists of silicate cement and tunnel slag powder.
[0062] The method for preparing the full-cavity slag concrete includes the following steps:
[0063] (1) Weigh each raw material according to the proportions and set aside;
[0064] (2) Take out half the mass of water and use a magnetic stirrer to fully dissolve the nano-Al2O3 in the mixed solution of water glass and 130kg water to obtain a nano-Al2O3 dispersion for later use.
[0065] (3) Pour silicate cement, tunnel slag powder, nano Al2O3 dispersion, water-absorbing resin and tunnel slag manufactured sand into a concrete mixer and dry mix for 1 minute. Then add the remaining amount of water and mix for 2 minutes to obtain the final product.
[0066] Example 2
[0067] This embodiment provides a nano-modified internal curing high geothermal resistant full-cavity concrete, comprising the following raw materials in parts by weight: 384 kg of ordinary silicate cement, 96 kg of tunnel cavity powder, 1300 kg of manufactured sand from tunnel cavities, 260 kg of water, 2.5 kg of nano-Al2O3, 0.4 kg of water-absorbing resin, and 10 kg of water glass.
[0068] Of which, by mass percentage, the mass of tunnel slag powder is 20% of the total mass of silicate cement and tunnel slag powder; the mass of nano-Al2O3 is 0.5% of the powder mass; the mass of water-absorbing resin is 0.08% of the powder mass; the mass of water glass is 2% of the powder mass; the mass ratio of manufactured sand to powder is 2.7:1, and the powder consists of silicate cement and tunnel slag powder.
[0069] The preparation method of the full-cavity slag concrete is the same as in Example 1.
[0070] Example 3
[0071] This embodiment provides a nano-modified internal curing high geothermal resistant full-cavity concrete, comprising the following raw materials in parts by weight: 336 kg of ordinary silicate cement, 144 kg of tunnel cavity powder, 1300 kg of manufactured sand from tunnel cavities, 260 kg of water, 2.5 kg of nano-Al2O3, 0.4 kg of water-absorbing resin, and 10 kg of water glass.
[0072] Of which, by mass percentage, the mass of tunnel slag powder is 30% of the total mass of silicate cement and tunnel slag powder; the mass of nano-Al2O3 is 0.5% of the powder mass; the mass of water-absorbing resin is 0.08% of the powder mass; the mass of water glass is 2% of the powder mass; the mass ratio of manufactured sand to powder is 2.7:1, and the powder consists of silicate cement and tunnel slag powder.
[0073] The preparation method of the full-cavity slag concrete is the same as in Example 1.
[0074] Example 4
[0075] This embodiment provides a nano-modified internal curing high geothermal resistant full-cavity concrete, comprising the following raw materials in parts by weight: 288 kg of ordinary silicate cement, 192 kg of tunnel cavity powder, 1300 kg of manufactured sand from tunnel cavities, 260 kg of water, 2.5 kg of nano-Al2O3, 0.4 kg of water-absorbing resin, and 10 kg of water glass.
[0076] Specifically, by mass percentage, the mass of tunnel slag powder is 40% of the total mass of silicate cement and tunnel slag powder; the mass of nano-Al2O3 is 0.5% of the powder mass; the mass of water-absorbing resin is 0.08% of the powder mass; the mass of water glass is 2% of the powder mass; and the mass ratio of manufactured sand to powder is 2.7:1, wherein the powder consists of silicate cement and tunnel slag powder.
[0077] The preparation method of the full-cavity slag concrete is the same as in Example 1.
[0078] Example 5
[0079] This embodiment provides a nano-modified internal curing high geothermal resistant full-cavity concrete, comprising the following raw materials in parts by weight: 240 kg of ordinary silicate cement, 240 kg of tunnel cavity powder, 1300 kg of manufactured sand from tunnel cavities, 260 kg of water, 2.5 kg of nano-Al2O3, 0.4 kg of water-absorbing resin, and 10 kg of water glass.
[0080] Of which, by mass percentage, the mass of tunnel slag powder is 50% of the total mass of silicate cement and tunnel slag powder; the mass of nano-Al2O3 is 0.5% of the powder mass; the mass of water-absorbing resin is 0.08% of the powder mass; the mass of water glass is 2% of the powder mass; the mass ratio of manufactured sand to powder is 2.7:1, and the powder consists of silicate cement and tunnel slag powder.
[0081] The preparation method of the full-cavity slag concrete is the same as in Example 1.
[0082] Example 6
[0083] This embodiment provides a nano-modified internal curing high geothermal resistant full-cavity concrete, comprising the following raw materials in parts by weight: 384 kg of ordinary silicate cement, 96 kg of tunnel cavity powder, 1300 kg of manufactured sand from tunnel cavities, 260 kg of water, 1.5 kg of nano-Al2O3, 0.2 kg of water-absorbing resin, and 5 kg of water glass.
[0084] Specifically, by mass percentage, the mass of tunnel slag powder is 20% of the total mass of silicate cement and tunnel slag powder; the mass of nano-Al2O3 is 0.3% of the powder mass; the mass of water-absorbing resin is 0.04% of the powder mass; the mass of water glass is 1% of the powder mass; and the mass ratio of manufactured sand to powder is 2.7:1, wherein the powder consists of silicate cement and tunnel slag powder.
[0085] The preparation method of the full-cavity slag concrete is the same as in Example 1.
[0086] Example 7
[0087] This embodiment provides a nano-modified internal curing high geothermal resistant full-cavity concrete, comprising the following raw materials in parts by weight: 384 kg of ordinary silicate cement, 96 kg of tunnel cavity powder, 1300 kg of manufactured sand from tunnel cavities, 260 kg of water, 3.5 kg of nano-Al2O3, 0.6 kg of water-absorbing resin, and 15 kg of water glass.
[0088] Specifically, by mass percentage, the mass of tunnel slag powder is 20% of the total mass of silicate cement and tunnel slag powder; the mass of nano-Al2O3 is 0.7% of the powder mass; the mass of water-absorbing resin is 0.1% of the powder mass; the mass of water glass is 3% of the powder mass; and the mass ratio of manufactured sand to powder is 2.7:1, wherein the powder consists of silicate cement and tunnel slag powder.
[0089] The preparation method of the full-cavity slag concrete is the same as in Example 1.
[0090] Comparative Example 1
[0091] This comparative example provides a full-tunnel muck concrete, which differs from Example 2 in that the tunnel muck powder is replaced with an equal mass of ordinary Portland cement.
[0092] This comparative example of full-cut concrete for tunnels includes the following raw materials by weight: 480 kg of ordinary Portland cement, 1300 kg of manufactured sand for tunnel cuttings, 260 kg of water, 2.5 kg of nano-Al2O3, 0.4 kg of water-absorbing resin, and 10 kg of water glass.
[0093] The preparation method of the full-cavity slag concrete is the same as in Example 1.
[0094] Comparative Example 2
[0095] This comparative example provides a full-cavity slag concrete, which differs from Example 2 in that it does not contain nano-Al2O3, water-absorbing resin, or water glass.
[0096] This comparative example of full-cut concrete includes the following raw materials by weight: 384 kg of ordinary Portland cement, 96 kg of tunnel muck powder, 1300 kg of manufactured sand from tunnel muck, and 260 kg of water.
[0097] The method for preparing the full-cavity slag concrete includes the following steps:
[0098] (1) Weigh each raw material according to the proportions and set aside;
[0099] (2) Pour ordinary silicate cement, tunnel slag powder and tunnel slag manufactured sand into a concrete mixer and dry mix for 1 minute, then add water and mix for 2 minutes to obtain the final product.
[0100] Comparative Example 3
[0101] This comparative example provides a full-tunnel muck concrete, which differs from Example 2 in that the tunnel muck powder is replaced with an equal mass of ordinary silicate cement, and no nano-Al2O3, water-absorbing resin and water glass are added.
[0102] This comparative example of full-cut concrete includes the following raw materials by weight: 480 kg of ordinary Portland cement, 1300 kg of manufactured sand for tunnel muck, and 260 kg of water.
[0103] The method for preparing the full-cavity slag concrete includes the following steps:
[0104] (1) Weigh each raw material according to the proportions and set aside;
[0105] (2) Pour ordinary silicate cement and tunnel slag into a concrete mixer and dry mix for 1 minute, then add water and mix for 2 minutes to obtain the final product.
[0106] Performance Measurement and Analysis
[0107] The 28-day compressive strength and 28-day flexural strength of the concrete obtained in the examples and comparative examples were determined according to GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete".
[0108] Tables 1 and 2 show the test results of the compressive strength and flexural strength of the full-cavity slag concrete obtained in Examples 1-6 and Comparative Examples 1-3 after curing at different temperatures.
[0109] The effects of high geothermal heat on the microstructure of the full-cavity slag concrete were investigated by curing it at different temperatures (20℃, 65℃, and 105℃) with and without the addition of the lifting material (Example 2). The results are as follows: Figure 7-12 As shown in the SEM images, the matrix density of the full-cavity slag concrete (Example 2) with added booster materials (water glass, water-absorbing resin, and nano-Al2O3) under high geothermal conditions is significantly better than that of the full-cavity slag concrete without booster materials (Comparative Example 2). The resulting concrete has smaller porosity and pore size, which is consistent with the above analysis results on mechanical properties and high geothermal resistance.
[0110] Table 1 shows the compressive strength of the full-cavity slag concrete obtained from the examples and comparative examples.
[0111]
[0112] Table 2 shows the flexural strength of the full-cavity slag concrete obtained from the examples and comparative examples.
[0113]
[0114] As shown in Tables 1 and 2, the mechanical properties and high geothermal resistance of the nano-modified internal curing resistant full-cavity slag concrete prepared by this invention have been significantly improved.
[0115] As can be seen from the comparison of Examples 1-5, with the increase of tunnel slag powder content, the high-strength hydration products in the whole-slag concrete decrease, and its resistance to high geothermal heat also gradually decreases. This is because the tunnel slag powder has low activity, the increase in cement replacement rate reduces the hydration products in the matrix, and the high geothermal effect further decomposes hydration products such as ettringite, leading to a decrease in mechanical properties. Therefore, considering the overall concrete performance and the utilization rate of tunnel slag powder, a content of 20% is the optimal content.
[0116] A comparison of Examples 2, 6, and 7 shows that increasing or decreasing the amount of nano-Al2O3, water-absorbing resin, and water glass relative to the powder (silicate cement and tunnel slag powder) all lead to a decrease in mechanical properties under high and low heat environments, especially changes in compressive strength. This is because the incorporation of nano-Al2O3 effectively reduces internal porosity in the matrix, making the microstructure denser, enhancing the interfacial strength between the matrix and aggregate, limiting crack propagation, and reducing crack width, thereby improving the mechanical properties of the mortar. Water glass reacts with larger, lower-strength Ca(OH)2 to form hydraulic calcium silicate colloids, increasing the strength of hydration products and the density of the matrix, thus enhancing the mechanical properties of the structure. Water-absorbing resin promotes cement hydration through internal curing, and the formation of high-strength hydration products increases the strength and density of the matrix.
[0117] As shown in Example 2 and Comparative Example 1, if the tunnel muck powder is replaced with an equal mass of ordinary Portland cement, the mechanical properties of the resulting all-muck concrete under high and low heat environments are similar. Therefore, this application, through the rational combination of the raw materials, achieves mechanical properties of the resulting all-muck concrete similar to those of cement concrete, thereby improving the utilization rate of tunnel muck.
[0118] The comparison between Example 2 and Comparative Example 2, and Comparative Example 1 and Comparative Example 3, shows that Comparative Example 2 and Comparative Example 3 did not contain nano-Al2O3, water-absorbing resin, or water glass in their raw materials. Compared to Example 2, the high geothermal resistance of the concrete in Comparative Example 2 was significantly reduced, especially in compressive strength. Compared to Comparative Example 1, the high geothermal resistance of the concrete in Comparative Example 3 was also significantly reduced, especially in compressive strength. This indicates that the addition of nano-Al2O3, water-absorbing resin, and water glass can significantly improve the high geothermal resistance of the whole-cavity slag concrete. This is because the water-absorbing resin releases water to form uniformly distributed pores, and the addition of water glass and nano-Al2O3 further refines the pores and increases the density of the matrix by promoting hydration. The fine pores and dense matrix provide stable transmission channels for water vapor transport and the release of thermal stress, thereby improving the high geothermal resistance of the whole-cavity slag concrete.
[0119] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A nano-modified, internally cured, high-geothermal-resistant, full-cavity slag concrete, characterized in that, Including the following parts by weight of raw materials: 200-500 parts silicate cement, 10-250 parts tunnel slag powder, 900-1800 parts manufactured sand for tunnel slag, 1-20 parts nano Al2O3, 0.1-2 parts water-absorbing resin, 1-20 parts water glass and 200-300 parts water; The tunnel rubble is composed of dolomite with a specific surface area ≥ 500 m². 2 / kg, CaCO3 mass content ≥85%; the tunnel muck is composed of dolomite with a particle size of 0.5mm~5mm; the nano-Al2O3 has a particle size of 10~100nm and a purity ≥99%; the water glass has a modulus of 3.3 and a solid content of 34%; The nano-modified internally cured high-geothermal-resistant full-cavity slag concrete is obtained through the following preparation method: (1) Weigh each ingredient according to the proportions and set aside; (2) Take out half the mass of water and fully dissolve the nano-Al2O3 in the mixture of water glass and half the mass of water to obtain a nano-Al2O3 dispersion for later use. (3) Mix silicate cement, tunnel slag powder, nano Al2O3 dispersion, water-absorbing resin and tunnel slag manufactured sand, mix for 1-2 minutes, then add the remaining water and stir for 2-4 minutes to obtain the final product.
2. The nano-modified internally cured high-geothermal-resistant full-cavity slag concrete as described in claim 1, characterized in that, Including the following parts by weight of raw materials: The composition includes 240-432 parts silicate cement, 48-240 parts tunnel slag powder, 900-1800 parts manufactured sand for tunnel slag, 1.5-3.5 parts nano Al2O3, 0.2-0.6 parts water-absorbing resin, 5-15 parts water glass, and 200-300 parts water.
3. The nano-modified internally cured high-geothermal-resistant full-cavity slag concrete as described in claim 1, characterized in that, By mass percentage, the mass of tunnel slag powder is 1% to 50% of the total mass of silicate cement and tunnel slag powder; the mass of nano-Al2O3 is 0.1% to 5% of the powder mass; the mass of water-absorbing resin is 0.01% to 0.5% of the powder mass; the mass of water glass is 0.1% to 5% of the powder mass; the mass ratio of manufactured sand to powder is (2 to 3):1; the powder consists of silicate cement and tunnel slag powder.
4. The nano-modified internally cured high-geothermal-resistant full-cavity slag concrete as described in claim 3, characterized in that, By mass percentage, the mass of tunnel slag powder is 10% to 50% of the total mass of silicate cement and tunnel slag powder; the mass of nano-Al2O3 is 0.3% to 0.7% of the powder mass; the mass of water-absorbing resin is 0.04% to 0.1% of the powder mass; and the mass of water glass is 1% to 3% of the powder mass.
5. The nano-modified internally cured high-geothermal-resistant full-cavity slag concrete as described in claim 1, characterized in that, The silicate cement is ordinary silicate cement with P·O 42.
5.
6. The nano-modified internally cured high-geothermal-resistant full-cavity slag concrete as described in claim 1, characterized in that, The particle size of the water-absorbing resin is 50~150 mesh.
7. A method for preparing nano-modified internally cured high-geothermal-resistant full-cavity slag concrete as described in any one of claims 1 to 6, characterized in that, Includes the following steps: (1) Weigh each ingredient according to the proportions and set aside; (2) Take out half the mass of water and fully dissolve the nano-Al2O3 in the mixture of water glass and half the mass of water to obtain a nano-Al2O3 dispersion for later use. (3) Mix silicate cement, tunnel slag powder, nano Al2O3 dispersion, water-absorbing resin and tunnel slag manufactured sand, mix for 1-2 minutes, then add the remaining water and stir for 2-4 minutes to obtain the final product.
Citation Information
Patent Citations
High-ground-temperature tunnel heat insulation lining concrete and preparation method thereof
CN105060836A
Thermal-insulation high-toughness carbonic tunnel hole slag geopolymer sprayed concrete and preparation method thereof
CN116102301A
Nano-enhanced internal curing sulfate-slag-resistant concrete and preparation method thereof
CN117865600A
